Intermolecular Reactions of Pyridyl Radicals with Olefins via Photoredox Catalysis - Seath, Ciaran P.; Jui, Nathan T. (Synlett, 2019)
Pyridines are valuable motifs in a number of bioactive and functional molecules. The chemoselective functionalization of these structures from stable and widely available starting materials is a meaningful goal. We have demonstrated selective formation of pyridyl radicals at any position (2-, 3-, 4-pyridyl), through the action of a reducing photoredox catalyst. These radicals readily engage alkenes to deliver high-value products. Alteration of the reaction medium has enabled the use of a diverse range of alkene subtypes in a highly divergent and chemoselective manner.1 Introduction2 Minisci-Type Pyridine Alkylation3 An Alternate Approach – Reductive Radical Formation4 Conjugate Addition of Pyridyl Radicals5 Radical Hydroarylation of Neutral and Rich Olefins6 Solvent-Based Chemoselectivity7 Summary and Outlook
Keywords: alkenes; catalysis; chemoselectivity; heterocycles; photochemistry; radicals; regioselectivity